The effect of trust on the fishing industry supply chain performance in Rokan Hilir Regency Riau Province, Indonesia - Yulinda, Eni; Supian, Kamisah; Saad, Mazni (IOP Publishing Ltd, 2022)
This research was conducted in August-October 2020 in Rokan Hilir Regency, the largest central of the fishing industry in Riau Province, Indonesia. The research objective to analyse the effect of trust on the fishing industry supply chain performance in the regency. Respondents were set 270 fishing companies based on the Slovin formula. They were taken purposively in four fishing centres, namely Panipahan (Pasir Limau Kapas district), Bagansiapiapi (Bangko), Kubu Babussalam, and Sinaboi. Collecting data using a closed questionnaire, containing a number of statements measured by a 7-point Likert scale. The data collected includes trust (credibility, top management capability, and government support), and supply chain performance (smooth of goods flow, financial flow, and information flow). Data analysed using the Structural Equation Modeling-Partial Least Square (SEM-PLS) method with the help of SmartPLS 3.3 software. The results showed that the trust has a positive and significant effect on the fishing industry performance in Rokan Hilir. This happens because the relationship between fellow entities of fishing industry supply chain occurs based on trust. The relationship between fishing companies (fisherman) and tauke (fish collectors, agents, and exporters) is based on patron-client ties, while the relationship between fellow tauke is based on family/blood ties. Both types of relationships have existed for years